Pengaruh Sistem Informasi Akuntansi Pengeluaran Kas Terhadap Pengendalian Internal - Siregar, Siti Aisyah; abdullah, Ikhsan; Chandra, Dody Salden (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
The purpose of this research is to determine and analyze the influence of the Cash Disbursement Accounting Information System on Internal Control at PT. Perkebunan Nusantara IV (Persero) Medan. In this research, an associative approach is used to determine the relationship between each variable. The data is presented in the form of quantitative data, namely testing and analyzing the data by calculating numbers and then drawing conclusions and testing. In this research, the objects studied were employees of PT. Perkebunan Nusantara IV (Persero) Medan with a population of 54 people and a sample of 54 people with sampling using saturated sampling. The results of the research are that the Cash Disbursement Accounting Information System has a significant effect on Internal Control at PT. Perkebunan Nusantara IV (Persero) Medan.